Effectiveness of person- and family-centered care transition interventions: a systematic review protocol - Backman, Chantal; Chartrand, Julie; Dingwall, Orvie; Shea, Beverley (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Care transitions from the hospital to home are critical to the sustainability of our health care system. Ineffective care transitions can be caused by high incidences of post-discharge adverse events, by poor communication with patients, and/or by inadequate information transfer between providers from the hospital to home. Any one of these can lead to fragmented care, high readmission rates, increased visits to the emergency department, and ultimately poor patient outcomes. Despite the ongoing improvement efforts of health care organizations, the efficacy of person- and family-centered care transition interventions on the quality of care and on the patient experience are not known. The aim of this systematic review is to critically analyze the body of evidence regarding the effectiveness of person- and family-centered care transition interventions on the quality of care, and the experience of patients. Methods We will conduct a systematic review using the Cochrane Handbook’s guidelines and will adhere to a standardized reporting format: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A comprehensive search strategy will be conducted in the following databases: MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, and the Cochrane Consumers and Communication Group. Following a two-step screening process, data including the full reference, objectives, target population, description of the intervention and control intervention, outcome measures, design, length of post-intervention follow-up period, and the study results will be extracted, synthesized, and reported. Risk of bias and quality of the studies will also be assessed. Discussion This systematic review will summarize and present the evidence base for person- and family-centered care transition interventions. This review will also inform further research and will lay the groundwork for more empirical studies on person- and family-centered care transitions. Specifically, the results of this systematic review may inform the development of measures to monitor safe and effective person- and family-centered transitions from the hospital to home. These results may also be important for policy makers, decision-makers, clinicians, and patients/families who are involved in navigating the health care system. Systematic review registration PROSPERO CRD42017067990